Stanzas in meditation : the corrected edition - Stein, Gertrude, 1874-1946; Hollister, Susannah; Setina, Emily; Retallack, Joan (New Haven [Conn.] : Yale University Press, 2011)
In the 1950s, Yale University Press published a number of Gertrude Stein's posthumous works, among them her incomparable Stanzas in Meditation. Since that time, scholars have discovered that Stein's poem exists in several versions: a manuscript that Stein wrote and two typescripts that her partner Alice B. Toklas prepared. Toklas's work on the second typescript changed the poem when, enraged upon detecting in it references to a former lover, she not only adjusted the typescript but insisted that Stein make revisions in the original manuscript. This edition of Stanzas in Meditation is the first to confront the complicated story of its composition and revision. Through meticulous archival work, the editors present a reliable reading text of Stein's original manuscript, as well as an appendix with the textual variants among the poem's several versions. This record of Stein's multi-layered revisions enables readers to engage more fully with the author's radically experimental poem and also to detect the literary impact of Stein's relationship with Toklas. The editors' preface and poet Joan Retallack's introduction offer insight into the complexities of reading Stein's poetry and the innovative modes of reading that her works require and generate. Students and admirers of Stein will welcome this illuminating new contribution to Stein's oeuvre.
On not not reading 'Stanzas in meditation' : pressures and pleasures of the text / by Joan Retallack -- The turning point : preface to the 1956 'Stanzas in meditation' / by Donald Sutherland -- The impossible : Gertrude Stein, review of the 1956 'Stanzas in meditation' / by John Ashbery -- Stanzas in meditation -- Appendix A. Publication history -- Appendix B. Reading text -- Appendix C. Editorial practices -- Appendix D. Notes.
"In association with the Beinecke Rare Book and Manuscript Library."
Print version record.
JSTOR
Keywords: Stein, Gertrude, -- 1874-1946.; Stein, Gertrude, -- 1874-1946 -- Criticism, Textual; Stein, Gertrude, -- 1874-1946; Stanzas in meditation (Stein, Gertrude); FICTION -- General; POETRY -- American -- General; Criticism, interpretation, etc